Tahfiz Students’ Interest and Awareness of Career Opportunities in the TVET Sector: A Gender Comparison - OMAR, MOHAMMAD AMSYAR; Masek, Alias (Research and Innovation in Technical and Vocational Education and Training, 2024)
The study examines the gender disparity in technical and vocational abilities among students attending Tahfiz schools, which mainly emphasize Islamic and Quranic teachings. The purpose of the study is to determine how interested and informed male and female Tahfiz students are of employment prospects. With 144 respondents, this study employs a quantitative survey approach. It finds that Tahfiz students generally felt highly interested in and informed of employment prospects. The study used comparative analysis, which enables comparison of its results with those of other studies. Importantly, there were no apparent gender variations in awareness or interest. According to the study, these results ought to direct the creation of a fair mix of inclusive educational and career programs in TVET, taking into account the many interests of Tahfiz students, thereby promoting the nation's professionalism and economic growth